Health parameters and antioxidant response in Black Sea whiting Merlangius merlangus euxinus (Nordmann, 1840) parasitized by nematode Hysterothylacium aduncum (Rud., 1802) - Skuratovskaya, Ekaterina; Skuratovskaya, Ekaterina; Zav'yalov, Andrey; Rudneva, Irina (Comunicata Scientiae, 2019)
Biometrical and biochemical parameters in healthy and parasitized by nematode Hysterothylacium aduncum Black Sea whiting Merlangius merlangus euxinus were studied. The increase of hepatosomatic index and decrease of spleen index in infected fish were found, while condition factor was similar in both groups. Antioxidant enzyme activities (superoxide dismutase (SOD), catalase (CAT), peroxidase (PER), glutathione reductase (GR) and glutathione-S-transferase (GST)) were higher in red blood cells in the parasitized fish as compared with the healthy animals. In the liver, the antioxidant response was not uniform: activities of SOD and GST decreased and activities of PER, GR and CAT increased in the infected individuals. The obtained results reflect host defense against oxidative stress caused parasitic infection. The tissue specific fluctuations of antioxidant response in parasitized and healthy fish are discussed. Data in this study can be used for understanding the defense mechanisms of fish against parasites.